Ingested foreign body in the common bile duct - Ranjan Dias; Parackrama Dharmaratne (Wolters Kluwer Medknow Publications, 2012)
We report a case of a 5-year-old boy who accidentally ingested a metal pin which was found inside the common bile duct on surgical exploration of duodenum and was removed through the ampulla of Vater. This is the first instance that an ingested metal pin in the common bile duct has been reported in the world literature.